The sense of place in designing coffee shops in Malaysia / Muhammad Haziq Shamsul Bahri and Mohamed Tajulz' Ariff Samsuddin - Shamsul Bahri, Muhammad Haziq; Samsuddin, Mohamed Tajulz' Ariff (College of Built Environment, 2023)
Coffee shops are considered 'third places' in urban environments, distinct from work and home, where people may gather, relax, and form connection.